UPAYA GURU SEJARAH KEBUDAYAAN ISLAM DALAM MENGATASI KEJENUHAN BELAJAR SISWA FULL DAY SCHOOL - Leniwati Leniwati (Jurnal Syaikh Mudo Madlawan: Kajian Ilmu-Ilmu Keislaman, 2024)
This research is motivated by the phenomenon of student boredom, lack of enthusiasm, and even falling asleep during the full-day school learning system at Madrasah Tsanawiyah Mathlabul Ulum. Based on this background, this study aims to identify the efforts of Islamic Cultural History (SKI) teachers in overcoming learning boredom and analyze the supporting and inhibiting factors that accompany it. Using a descriptive qualitative approach, this study involved one SKI teacher and four eighth-grade students as subjects and key informants. Data were collected comprehensively through observation techniques, in-depth interviews, and documentation, which were then processed using data analysis techniques in the form of data reduction, data presentation, and systematic conclusion drawing. The results revealed that SKI teachers made various strategic efforts such as preparing lesson schedules effectively, creating a conducive initial learning atmosphere through greetings and seating arrangements, and providing strong motivation in the form of rewards and praise. In addition, the use of varied learning methods and media, including the use of video projectors, proved crucial in maintaining student enthusiasm. Supporting factors for this success include the availability of adequate infrastructure and positive internal student motivation. On the other hand, the effectiveness of these efforts is still limited by several key inhibiting factors, such as student laziness, limited availability of certain media, and limited class time for in-depth material delivery. Overall, the synergy between teacher creativity and supportive school facilities is key to minimizing student academic burnout in a full-day school system.